QUESTIONING TECHNIQUES AND HIGH ORDER THINGKING IN STUDENTS LEARNING GROUP - Ria Dhatun Nikmah (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
Questioning is an essential strategy for effective communication. This study examined questioning techniques used by students and the Critical thinking processes involved in questioning. There was also an attempt to find out the differences between the patterns of using questions between the two groups. Data were sourced from student learning group through audio and video taping the sessions and were analyzed using types of questioning. Findings indicated that students asked higher order in level questions such as open - ended, interpretive, and evaluative, inquiry, inferential, and synthesis, while most students raised lower cognitive questions including facts, closed, direct, recall, and knowledge type questions. It is suggested that using higher level questioning technique, more frequently used by teacher as more competent speakers in comparison to students, can foster learning and students are required to attend higher levels of questioning techniques to enhance their speculative, inferential and evaluative thinking ability